Bounds for the Largest Laplacian Eigenvalue of Weighted Graphs. (9th April 2013) - Sorgun, Sezer
Abstract : LetG be weighted graphs, as the graphs where the edge weights are positive definite matrices. The Laplacian eigenvalues of a graph are the eigenvalues of Laplacian matrix of a graphG . We obtain two upper bounds for the largest Laplacian eigenvalue of weighted graphs and we compare these bounds with previously known bounds.